If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 12 + (x + -1)(-4) Reorder the terms: y = 12 + (-1 + x)(-4) Reorder the terms for easier multiplication: y = 12 + -4(-1 + x) y = 12 + (-1 * -4 + x * -4) y = 12 + (4 + -4x) Combine like terms: 12 + 4 = 16 y = 16 + -4x Solving y = 16 + -4x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 16 + -4x
| 67-4x=13-10x | | (7x^2)(5x^3)=35x^5 | | 9.6f+5.8(20)= | | 4t+3500=15t | | 3x+13=-17-2x | | 30=2x+5y | | -.80(x-4)=8 | | 8x-13=3x+5 | | x=16x^3+-12x^2+-70x+36 | | x-4=-8+x | | 22h+10=98 | | 13x-17=17+12x | | 3m-20=100 | | x-5=2-3x-2(x+1) | | f(x)=16x^3-12x^2-70x+36 | | 3y+5x= | | -5(t-3)+2t=-30 | | 2x-16=-(7x+16) | | x-5=-5x | | .33m+6=.66m+9 | | -11-k=k+1 | | 5+5n=14 | | x+8(-1-5x)=304 | | (9b+3)-(-2b+6)= | | -3y-12=3y+22 | | -3(2t-5)=2(4t+7) | | 2b+13=21 | | -4+n=2n+8 | | 14z-6=2z+18 | | 7=-14y | | 4+3p=10 | | 16-.75n=.25n+7 |